1996
DOI: 10.1095/biolreprod55.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Suppression in the Secretion of Follicle-Stimulating Hormone and Luteinizing Hormone, and Ovarian Follicle Development in Heifers Continuously Infused with a Gonadotropin-Releasing Hormone Agonist1

Abstract: A novel experimental model was developed in cattle to investigate the requirement for FSH and LH during ovarian follicle growth and development. On Day 5 of the estrous cycle, 7 heifers were each implanted with an osmotic minipump containing a GnRH agonist (GnRHa), Buserelin (release rate, 2.5 micrograms/h). Another 7 heifers served as controls. Each minipump was replaced 28 days later with a second pump, which was left in place for a further 20 days. Blood samples were collected daily throughout the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
1
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(101 citation statements)
references
References 37 publications
8
81
1
11
Order By: Relevance
“…This time period coincides with the time when peripheral FSH concentrations reach a nadir (Adams et al 1992), supporting the hypothesis that dominant follicle selection is associated with a shift from FSH to LH dependence. Administration of a gonadotropin releasing hormone (GnRH) agonist that suppressed circulating concentrations of LH, but not FSH, resulted in follicular arrest at 7 to 9 mm in diameter (Gong et al 1996). The preceding data suggest that LH is important for continued follicular development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This time period coincides with the time when peripheral FSH concentrations reach a nadir (Adams et al 1992), supporting the hypothesis that dominant follicle selection is associated with a shift from FSH to LH dependence. Administration of a gonadotropin releasing hormone (GnRH) agonist that suppressed circulating concentrations of LH, but not FSH, resulted in follicular arrest at 7 to 9 mm in diameter (Gong et al 1996). The preceding data suggest that LH is important for continued follicular development.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, we utilized the GnRH agonist (GnRHa) model developed by Gong et al (1996). Previous studies (Gong et al 1996, Garverick et al 2002 have shown that this treatment results in suppression of the gonadotropins, FSH and LH, which subsequently results in suppression of follicular growth to , 5 mm in diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De fato, alguns autores relataram que os folículos tornam-se responsivos as gonadotrofinas exógenas em um intervalo pós-parto inferior a 30 dias. 3,41 Segundo Crowe et al 42 , o eCG ao suprir a falta de LH, proporciona ao folículo a capacidade de se desenvolver até a fase pré-ovulatória, considerando que tal evento é dependente de LH 43 . Verificou-se que a ativação dos receptores de LH e FSH no folículo promove um aumento na concentração de adenosina monofosfato cíclico (AMPc) intrafolicular, evento que promoveria a ativação de enzimas intracelulares que contribuiriam para incrementar produção de E 2 pelo folículo.…”
Section: Resultsunclassified
“…This takes 3 to 4 days. LH pulses are indispensable for follicle development beyond 9 mm in diameter (GONG et al, 1996;KANITZ et al, 2001). Endocrine pattern of gonadotropins is followed by characteristic changes in follicles.…”
Section: Dominancementioning
confidence: 99%